The Effect of Reducing Prices for Kuna-Kini MSME Products During the Covid-19 Pandemic on Sales Results - Misrofingah; Arif Riyanto (Journal of Research in Business, Economics, and Education, 2021)
During this Covid-19 pandemic, small industries have a fairly large role in supporting the economy of the community, even during this time of crisis that hit Indonesia, many small industries were able to survive in this crisis situation. The strength of small industry so that it is able to survive is because small industry is very flexible and very quick to respond to changes, besides that most of the raw materials and natural resources used are local. But not all small industries use local raw materials, there are some that use imported raw materials, but the amount is relatively small. Due to its local nature, small industries can still produce. Small industries are mostly carried out in rural areas, this is done because of the consideration of various aspects, namely the low wages of labor, a lot of available labor, and the availability of raw materials that are easily available. This aspect can attract residents in rural areas to open businesses both as side businesses and main businesses apart from farming and other businesses. With the increasing questions about product competition from MSMEs, the strategy of reducing selling prices during this pandemic, in this case is implemented by examining the MSME products "Kuna now which has a strategy of reducing selling prices. sales results. It can be concluded that the decrease in selling price has a significant effect on sales results. It is better if Kuna-Kini MSMEs always improve the skills (professionalism) of employees and also need to place the right human resources in handling the promotion section, which in today's digital era can be done through social media, with the hope of having a positive impact on sales results.